Non-Destructive Testing of Honeycomb CFRP Panel by Means of Shearography; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Burkov M. V. Mikhail Vladimirovich (2018, 2018)
Title screen